Egg Quality Characteristics, Phenotypic Correlations and Prediction of Egg Weight in Three (Naked Neck, Frizzled Feather and Normal Feathered) Nigerian Local Chickens - Udoh , U.H.; Okon, B.; Udoh, A.P. (International Journal of Poultry Science, 2012)
A study was conducted to determine egg quality characteristics, phenotypic correlations and prediction of egg weight from egg quality parameters in three varieties (naked neck, frizzled feather and normal feathered) of local chickens in Akwa Ibom State, Southeastern Nigeria. A total of 600 eggs (200 each of naked neck, frizzled feather and normal feathered varieties) were collected. External and internal defects were computed and expressed as percentage of total egg production and summed up to obtain the total defects score for each variety. Egg quality parameters were compared between varieties using Multivariate General Linear Model of SPSS version 17.0 for ANOVA. Means were tested using Duncan’s Multiple Range Test. Phenotypic correlations of egg quality parameters and prediction of egg weight using yolk weight, yolk width and albumen weight was done. Lowest total defects score (11.00%) was recorded for frizzled feather, 11.63% for naked neck and the highest (12.65%) for normal feathered. Egg weight differed significantly (p<0.05) among the 3 varieties with the values of 45.72 g, 44.72 g and 41.91 g for naked neck, normal feathered and frizzled feather varieties respectively. Yolk weight, yolk width, yolk height, yolk index, albumen weight, albumen width, albumen index and shell thickness were not significantly different (p>0.05). Mean highest value of 82.49% for haugh unit by naked neck was significantly different (p<0.05) from 77.57% by normal feathered and 77.01% by frizzled feather. Naked neck had best egg quality characteristics, followed by normal feathered and lastly the frizzled feather. In the normal feathered variety, strong, positive and significant (p<0.01) correlations were observed between egg weight and yolk weight (0.773) and albumen weight (0.797); yolk weight and albumen weight (0.567); yolk index and yolk height (0.715); haugh unit and albumen height (0.954) and albumen index (0.863). In the naked neck, strong, positive and significant (p<0.01) correlations were observed between egg weight and yolk weight (0.611) and albumen weight (0.768); haugh unit and albumen height (0.934). In the frizzled feather, strong, positive and significant (p<0.01) correlations were observed between egg weight and yolk weight (0.567) and albumen weight (0.680); haugh unit and albumen height (0.883) and albumen index (0.856). These parameters would give rapid improvements if selected together in the respective varieties. Egg weight was predictable from albumen weight with sufficient Reliability (R) of 0.77. 0.77 and 0.68 for normal feathered, naked neck and frizzled feather varieties respectively. Although many egg quality characteristics have strong genetic basis, it is necessary to implement a total quality management programme to maintain consistently good quality throughout the egg production cycle.